2015
DOI: 10.1002/mren.201500022
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Polyethylene Nanofibrils Over rac‐Et(Indenyl)2ZrCl2/MAO Catalyst Supported on Silica Nanotubes

Abstract: The morphology of polyethylene synthesized over rac-Et(indenyl) 2 ZrCl 2 /MAO catalyst supported on silica nanotubes of anodized aluminum oxide (AAO) template and on liberated silica nanotubes have been studied. A silica nanotube is quickly filled up with polymer, which extrudes out to the bulk liquid phase as nanofibrils of 30-35 nm diameter with high crystallinity. When silica nanotubes are liberated from the AAO template and deposited with catalysts, the polyethylene nanofibrils formed at the outer surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To observe the nascent morphology of olefin polymers in the proximity of catalyst sites, specially designed catalyst support materials will be useful. For example, flat surface silica can be used as a catalyst support and other support geometries such as spherical solid silica nanoparticles and silica nanotubes have also been used . Since these support materials do not have complex internal or secondary structures, the deposition of catalyst is possible only on the exposed solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To observe the nascent morphology of olefin polymers in the proximity of catalyst sites, specially designed catalyst support materials will be useful. For example, flat surface silica can be used as a catalyst support and other support geometries such as spherical solid silica nanoparticles and silica nanotubes have also been used . Since these support materials do not have complex internal or secondary structures, the deposition of catalyst is possible only on the exposed solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The same approach can also be extended to other support geometries, such as silica nanotubes and solid silica nanoparticles. For example, when ethylene was polymerized over metallocene catalysts deposited on solid silica nanoparticles and silica nanotubes, it was observed that the basic polyethylene (PE) morphology was a nanofibril of diameter 30–50 nm …”
Section: Introductionmentioning
confidence: 99%
“…Some of these silica supports provide uniform distribution of catalysts on the support surface and improved accessibility of monomers during the polymerization. They are, for example, mesoporous silica materials such as MCM‐41, SBA‐15, pseudoinverse opal silica microparticles, and other various silica materials having unique morphologies . Among these, the mesoporous silica materials with controlled pore size and pore volume have been illustrated to accommodate large metallocene catalysts better than conventional porous microsilica particles.…”
Section: Introductionmentioning
confidence: 99%